Intercropping Amomum villosum enhances soil stratification, nutrient complementarity, and microbial communities in rubber plantations - Du, Huabo; Lin, Yuchen; Qi, Meijun; Qu, Peng; Xu, Zhenhuai; Lin, Rong; Xie, Chun; Xiao, Tengwei; Dong, Shilang; Wang, Butian; Ge, Yu (Frontiers in Microbiology, 2026)
Intercropping is widely promoted to sustain soil function, yet evidence for its application in rubber-based agroforestry, particularly with the shade-tolerant herb Amomum villosum, is limited. We evaluated whether A. villosum intercropping improves soil properties and reorganizes microbiomes across the vertical profile of mature rubber plantations. Soil samples were taken at 0–10, 10–20, and 20–30 cm depths in both intercropped and monoculture stands. Physical and chemical properties were quantified, and bacterial (16S rRNA V3–V4) and fungal (ITS2) communities were analyzed using high-throughput amplicon sequencing with depth-resolved data on diversity, composition, and functional inference (FAPROTAX, FUNGuild). Intercropping consistently improved soil structure and fertility, with the strongest effects at 0–10 cm. Total porosity (12%), organic matter (38.9%), alkali-hydrolyzable nitrogen (75.4%), and available phosphorus (131%) were markedly higher than in monoculture. Benefits extended to mid-depth with a 65.2% increase in alkali-hydrolyzable nitrogen. Microbial richness (bacteria and fungi) increased, and communities separated clearly by treatment and depth. Intercropped soils showed higher relative abundances of copiotrophic and particle-attached phyla (e.g., Proteobacteria, Planctomycetota), while Acidobacteriota and several Chloroflexi declined. Nitrospirota increased with depth. Fungal trophic structure shifted away from pathotrophs at 20–30 cm and toward symbiotrophs, particularly arbuscular mycorrhizal lineages, at subsurface layers. Functional predictions indicated greater potential for nitrogen transformations (e.g., nitrogen fixation, nitrification), greater C₁/hydrocarbon utilization, and a reduced bacterial plant-pathogen signal under intercropping. Collectively, A. villosum intercropping reorganizes the soil environment and microbiome in mutually reinforcing ways—improving physical structure, enlarging near-term nitrogen supply, and favoring beneficial fungal guilds. These depth-resolved effects help explain the agronomic appeal of rubber–A. villosum systems and support their wider deployment in rubber plantations.